Treatment of pre-eruptive intracoronal resorption: A systematic review and case report - Van Nhat Thang Le; Jae-Gon Kim; Yeon-Mi Yang; Dae-Woo Lee (Elsevier, 2020)
Background/purpose: Pre-eruptive intracoronal resorption (PEIR) is usually detected accidently in radiographs. However, treatment modality is still not reported systematically. The current study aimed to conduct a systematic review of the treatment modality of PEIR case reports and to report a case on the preservation of a vital pulp with surgical exposure in permanent maxillary canine. Materials and methods: We systematically searched case reports from PubMed/MEDLINE, EMBASE, and Web of science databases. The treatment modality, suspected etiology, and follow up periods were collected from each study and reviewed by two authors independently. Results: The initial search identified 100 studies. After the title/abstract screening, 37 articles received a full-text reading; and finally, 24 articles (29 patients and 37 affected teeth) were selected for the final review. Among the 24 unerupted teeth, surgical opening and restoration treatment of PEIR was chosen as a high priority for treatment options (n = 9, 36%). Among the 13 erupted teeth, restoration was applied for the prevention such as developing in size and fracture (n = 4, 31%). Conclusion: According to this systematic review, treatment modalities were based on the progressive nature of the lesion size and eruption state to establish the optimal approach for each patient. Clinicians should take into account the eruption status, lesion progression, the size of the lesion, and the degree of pulp involvement.